1997
DOI: 10.1074/jbc.272.27.17176
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Myosin I in the Nucleus

Abstract: We produced and affinity-purified polyclonal antibodies to adrenal myosin I. These antibodies recognize adrenal myosin I by Western blot analysis (116 kDa) and inhibit the actin-activated ATPase activity of purified adrenal myosin I. They also recognize a 120-kDa protein in extracts prepared from many different cell lines. Fluorescence microscopy demonstrated the presence of immunoreactive material in the perinuclear region, the leading edges, and the nuclei of 3T3 cells. Fluorescence microscopy also demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 46 publications
1
88
0
Order By: Relevance
“…Recently, the nuclear localisation of actin itself (Scheer et al, 1984;Gonsior et al, 1999), actin-related proteins (Arps) (Cairns et al, 1998;Harata et al, 1999;Harata et al, 2000) and a number of actin binding proteins (Nowak et al, 1997;Giesemann et al, 1999;Pestic-Dragovich et al, 2000;Skare et al, 2003) has been reported. Although the functions of nuclear actin are far from being fully understood, it has been proposed that it might be involved in chromatin remodelling (Zhao et al, 1998;Shen et al, 2003), mRNA processing and transport (Hofmann et al, 2001;Percipalle et al, 2001;Percipalle et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the nuclear localisation of actin itself (Scheer et al, 1984;Gonsior et al, 1999), actin-related proteins (Arps) (Cairns et al, 1998;Harata et al, 1999;Harata et al, 2000) and a number of actin binding proteins (Nowak et al, 1997;Giesemann et al, 1999;Pestic-Dragovich et al, 2000;Skare et al, 2003) has been reported. Although the functions of nuclear actin are far from being fully understood, it has been proposed that it might be involved in chromatin remodelling (Zhao et al, 1998;Shen et al, 2003), mRNA processing and transport (Hofmann et al, 2001;Percipalle et al, 2001;Percipalle et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Lately, there has been increasing evidence for the presence of cytoskeletal proteins in the nucleus, such as actin itself (Scheer et al, 1984;Gonsior et al, 1999), actin-related proteins (Arps) (Cairns et al, 1998;Harata et al, 1999;Harata et al, 2000) and a number of different actin binding proteins (Nowak et al, 1997;Giesemann et al, 1999;Pestic-Dragovich et al, 2000;Skare et al, 2003). Although the functions of these proteins in the nucleus are still under investigation, there is evidence that they are involved in activities ranging from nuclear assembly and shape changes to DNA replication and transcription (Rando et al, 2000;Olave et al, 2002;Pederson and Aebi, 2002;Shumaker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear and cytosolic isoforms are identical except for 16 extra residues at the N-terminus of the nuclear isoform (33,58). NMI is necessary for mRNA transcription in vitro, binds directly to the large subunit of RNA polymerase II, and is proposed to facilitate movement of the transcription machinery (33,59) or chromatin itself during transcription (47).…”
Section: Implications Of Emerin Binding Directly To Nuclear Myosin Imentioning
confidence: 99%
“…NMI contains a unique N-terminal peptide, because the transcription start site for NMI is in an exon that is located upstream to the start site for cytoplasmic myosin IC (PesticDragovich et al, 2000). Functionally, NMI colocalizes with RNA polymerase I (Fomproix and Percipalle, 2004;Nowak et al, 1997) and RNA polymerase II (Fomproix and Percipalle, 2004;Nowak et al, 1997;Pestic-Dragovich et al, 2000), and co-purifies and coimmunoprecipitates with both polymerases (Pestic-Dragovich et al, 2000;Philimonenko et al, 2004). Additionally, NMI-specific antibodies inhibit transcription by these polymerases both in vivo and in vitro (Fomproix and Percipalle, 2004;Pestic-Dragovich et al, 2000;Philimonenko et al, 2004).…”
Section: Introductionmentioning
confidence: 99%